The P* model as a general identity to analyze and forecast the behavior of the inflation rate in the economy of Puerto Rico - Carlos A. Rodríguez Ramos (Economics and Econometrics Research Institute (EERI), 2003)
In this work the P* model is used to analyze and forecast the inflation rate in the economy of Puerto Rico. This model is based on two essential points: the first one is to identify the inflationary potential of an economic system through the estimation of the price level to which the inflation tends to adjust in the long run. The second, points that the price level will be adjust, in the long run, to the forecast of the model. Given the way in which the monetary sector in Puerto Rico its constituted, the model needs to complement with U.S.A. monetary variables , such as, monetary supply, to forecast the inflation. The results indicate a long run relationship between the monetary supply of United States (M1) and the price level, the real production and the island<92>s preferential interest rate. The final model is a good representation of the generating process of information (GPI) and it could be used for forecasting purposes. The same predicts the development of inflation better than the two ARIMA models previously selected.
Keywords: C32; C52; C53; 330; Econometric Modeling; Time Series Analysis; Forecasting Methods; Monetary Economics